ANALYSIS OF STUDENTS CHEMICAL BONDING MISCONCEPTIONS USING TWO-TIER DIAGNOSTIC TEST - Putri, Nabilah Mustika; Rahmawati, Yuli; Irwanto, Irwanto (FKIP USK, 2024)
This study aims to identify the misconceptions of 10th-grade students of a Senior High School (SMA N 1) Ciawi Bogor on chemical bonding by using a two-tier diagnostic test consisting of nine questions. The research method that was carried out was quantitative research with adescriptive approach. The participants of this study were classes X-2, X-4, and X-8 of SMAN 1 Ciawi in the academic year 2023/2024, with a total sample of 96 students taken from three classes using purposive sampling. Moderate misconceptions concerning ionic bonding have been discovered in the responses provided by the students for questions 1 and 2, with percentages of 37.50 and 34.38%, respectively. In Question 3, which covered lattice and intermolecular forces on silicon carbide, misconceptions among students were found to be 72.92%, indicating a high level of misconception. The percentage of students experiencing misconceptions about ionic bonding in question 4 (58.33%) was considered moderate. Students' misconceptions about bonding and intermolecular forces on magnesium oxide were determined to be relatively low, at 30.21%. Students who experienced misconceptions about the conductivity of graphite (Question 6) were 43.75%, which can be categorized as moderate misconceptions. In Question 7 about sulfur, student misconceptions were observed at 15.63%, but there were 47.92% who did not have prior knowledge about sulfur as a simple molecular compound. When asked about the differences in intermolecular forces on water and hydrogen sulfide, the percentage of students who had misconceptions was observed at 50.00%, then on the concept of lattice and intermolecular forces on macromolecules at 25.00%. These results are also influenced by students' prior knowledge of macromolecules, which is quite limited. Teachers and educators can employ some potential futuristic instructional methods to help students understand chemical bonding more efficiently, such as implementing VR and AR simulations, integration of gamification and game-based learning, andvirtual field trips and interactive demonstrations.